2012
DOI: 10.1371/journal.pone.0032521
|View full text |Cite
|
Sign up to set email alerts
|

Structure Based Design and Synthesis of Peptide Inhibitor of Human LOX-12: In Vitro and In Vivo Analysis of a Novel Therapeutic Agent for Breast Cancer

Abstract: Human breast cancer cell proliferation involves a complex interaction between growth factors, steroid hormones and peptide hormones. The interaction of growth factors, such as epidermal growth factor (EGF), with their receptors on breast cancer cells can lead to the hydrolysis of phospholipids and release of fatty acid such as arachidonic acid, which can be further metabolized by cyclooxygenase (COX) and lipoxygenase (LOX) pathways to produce prostaglandins. The high concentration of prostaglandins has been as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 23 publications
3
11
0
Order By: Relevance
“…These findings strongly supports that the serum level of 5-LOX can be a good blood-based non-invasive marker for the early detection of the breast cancer in the clinical setup. Previously, we reported the inhibition of 12-LOX, by YWCS peptide inhibitor, effectively induced cytotoxicity and apoptosis in MCF-7 and MDA-MB-231 breast cancer cells (11). As the active site of 12-LOX and 5-LOX are homologous, the same peptide YWCS were docked with the 5-LOX protein and found to have strong interaction in the binding site.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…These findings strongly supports that the serum level of 5-LOX can be a good blood-based non-invasive marker for the early detection of the breast cancer in the clinical setup. Previously, we reported the inhibition of 12-LOX, by YWCS peptide inhibitor, effectively induced cytotoxicity and apoptosis in MCF-7 and MDA-MB-231 breast cancer cells (11). As the active site of 12-LOX and 5-LOX are homologous, the same peptide YWCS were docked with the 5-LOX protein and found to have strong interaction in the binding site.…”
Section: Discussionmentioning
confidence: 91%
“…Numerous autonomous studies by different groups of researchers now support the correlation between the expression of 5-LOX and cancer cell viability, invasion through extracellular matrix destruction, cell migration, proliferation, metastasis and activation of anti-apoptotic signaling cascades, which makes the 5-LOX effective therapeutic regimen (28). The earlier evidences interpreted the efficacy of peptide, YWCS, to inhibit 12-LOX and its utilization as an anti-breast cancer molecule by inducing cytotoxicity and apoptosis in MCF-7 and MDA-MB-231 breast cancer cells (11). In this study, the peptide, YWCS was found to be active against 5-LOX also and thus adding further information regarding the mechanism through which it induce cytotoxicity in breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The masked lysine was coupled onto the Rink Amide MBHA resin. HBTU and HOBt were used to enhance the coupling rate [55], [56], [57]. The Fmoc was then deprotected to allow for (3-carboxypropyl)TPP + conjugation through its carboxylic acid group forming an amide bond.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, the development of peptides and peptidomimetics as potential candidates to remedy various diseases has attracted considerable attention in both academia and the pharmaceutical industry 20,21,22. This is due to the high specificity, solubility, stability, and unique pharmacokinetic characteristics of peptides compared with large proteins or small molecules 23.…”
Section: Introductionmentioning
confidence: 99%